Isolation and identification of squash blossom end rot and fruit rot fungi and their control - Nidal Younis Al-Murad; Selda Mohammed Baker (Mesopotamia Journal of Agriculture)
Alternaria alternate, Choanephora cucurbitarum, Fusarium culmorum, Fusarium proliferatum Fusarium sporotrichioides, were isolated from squash plants showed blossom end rot symptoms,with different isolation frequencies.  Pathogenicity test for previous fungi were fulfilled. In laboratory trials, Amcoton was  applied to PDA to determine its  effect  on dry weight of  previous fungi, the result showed significant inhibitions on dry weight to C. cucurbitarum and   F.culmorum with  16.12% when it was used with 20 mg  and 10 mg/ L respectively,  while  Amcoton application showed   activation effect to  A.alternata dry weight  with  activation  percent 41.3 % when it was used with 20 mg / L. Amcoton application also caused   significant  inhibition to fungal mycelium growth  the highest  inhibition  was recorded with C.cucurbitarum 23,54 % ,while Activation effective was observed with  A.alternata   with 11.2%